Structure-Activity Relationship Study of the Neuritogenic Potential of the Glycan of Starfish Ganglioside LLG-3 ‡ - Megumi Yamagishi; Ritsuko Hosoda-Yabe; Hideki Tamai; Miku Konishi; Akihiro Imamura; Hideharu Ishida; Tomio Yabe; Hiromune Ando; Makoto Kiso (Marine Drugs, 2015)
LLG-3 is a ganglioside isolated from the starfish Linchia laevigata. To clarify the structure-activity relationship of the glycan of LLG-3 toward rat pheochromocytoma PC12 cells in the presence of nerve growth factor, a series of mono- to tetrasaccharide glycan derivatives were chemically synthesized and evaluated in vitro. The methyl group at C8 of the terminal sialic acid residue was crucial for neuritogenic activity, and the terminal trisaccharide moiety was the minimum active motif. Furthermore, the trisaccharide also stimulated neuritogenesis in human neuroblastoma SH-SY5Y cells via mitogen-activated protein kinase (MAPK) signaling. Phosphorylation of extracellular signal-regulated kinase (ERK) 1/2 was rapidly induced by adding 1 or 10 nM of the trisaccharide. The ratio of phosphorylated ERK to ERK reached a maximum 5 min after stimulation, and then decreased gradually. However, the trisaccharide did not induce significant Akt phosphorylation. These effects were abolished by pretreatment with the MAPK inhibitor U0126, which inhibits enzymes MEK1 and MEK2. In addition, U0126 inhibited the phosphorylation of ERK 1/2 in response to the trisaccharide dose-dependently. Therefore, we concluded that the trisaccharide promotes neurite extension in SH-SY5Y cells via MAPK/ERK signaling, not Akt signaling.